Bioaktivitas Campuran Ekstrak Biji Barringtonia asiatica L. (Kurz.) (Lecythidaceae) dan Getah Azadirachta indica A. Juss. (Meliaceae) terhadap Larva Spodoptera litura F. (Lepidoptera: Noctuidae) - Indah Meutia Arisanti; Danar Dono (Fakultas Pertanian Universitas Padjadjaran, 2015)
ABSTRACTBioactivity of mixed seed extract of Barringtonia asiatica l. (kurz.) (lecythidaceae) and sap of Azadirachtaindica A. Juss. (meliaceae) against larvae of Spodoptera litura f. (lepidoptera: noctuidae)Barringtonia asiatica and Azadirachta indica are known to have variety of chemical compounds that haspotency to be developed as botanical pesticides. The study aimed to determine insecticidal toxicity of B.asiatica seed extract and A. indica sap and their mixture. The experiment was carried out in the Laboratoryof Pesticides and Application Technology, Department of Plant Pests and Diseases, Faculty of Agriculture,Universitas Padjadjaran. The experiments were conducted either on toxicity test of the seed extract of B.asiatica and the sap of A. indica singly or their mixture based on the comparison of LC95. Toxicity testing wasperformed using a leaf-residue feeding method on the instar I of Spodoptera litura larvae. The resultsshowed that seed extractof B.asiatica has a moderate toxicity to S.liturawith the LC50 value of 0.491% andaffected body weight of the larvae. The sap of A.indicahas had slightly low toxicity with the LC50 value of1.310%. The mixture of B. asiatica seed extract and A. Indica sap (based on ratio of 4.1%of B. asiaticacompare to 4.9% of A. Indica) has LC50 value of 0.970% (slightly low toxicity) and the LC95 value of 15.99%that was antagonistic on the LC95 level with Cotoxicity Ratio value of 0.23% on 12 days after treatment.Keywords: Cotoxicity ratio, independent joint action, Barringtonia asiatica, Azadirachta indica, SpodopteralituraABSTRAKBarringtonia asiatica dan Azadirachta indica diketahui memiliki berbagai senyawa kimia yang berpotensidikembangkan sebagai pestisida nabati. Penelitian yang bertujuan untuk mengetahui toksisitas ekstrak biji B.asiatica dan getah A. indica serta campurannya telah dilakukan di Laboraturium Pestisida dan TeknikAplikasi, Departemen Hama dan Penyakit Tumbuhan, Fakultas Pertanian, Universitas Padjadjaran.Penelitian meliputi uji toksisitas ekstrak biji B. asiatica dan getah A.indica secara tunggal, dan pengujiancampuran ekstrak biji B. asiatica dan getah A.indica berdasarkan pada perbandingan LC95. Pengujiantoksisitas dilakukan dengan metode celup pakan pada larva instar I Spodoptera litura. Hasil penelitianmenunjukkan bahwa ekstrak biji B. asiatica bersifat toksik sedang terhadap S. litura dengan nilai LC50sebesar 0,491% dan berpengaruh terhadap bobot basah larva. Getah A. indica bersifat toksik ringan dengannilai LC50 1,310%. Campuran ekstrak biji B. asiatica dan getah A. indica berdasarkan rasio 4,1% B. asiaticaberbanding 4,9% A. indica memiliki LC50 sebesar 0,970% (toksisitas ringan) dengan LC95 sebesar 15,99% dandinyatakan bersifat antagonis pada LC95 dengan nilai Nisbah Kotoksisitas 0,23% pada 12 hari setelahaplikasi.Kata kunci: Nisbah Kotoksisitas, Kerja bersama bebas, Barringtonia asiatica, Azadirachta indica, Spodopteralitura